First record of Adelophryne baturitensis hoogmoed, borges & Cascon, 1994 for the state of Pernambuco, northeastern Brazil (Anura, Eleutherodactylidae, Phyzelaphryninae) - Loebmann, Daniel (2011)
Laboratório de Ecologia de Vertebrados Terrestres Instituto de Ciências Biológicas Universidade Federal do Rio Grande - FURG, Av. Itália, Km 8, CEP 96201-900, Rio Grande, RS